(3QSGdI aj GdgfOHGs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s ((3eMeO Hf bWH GdWHjH s)
(3ChdgG (B:s
(3SFd GdTjN ai YdI CeQg HGSJYeGd GdgfOHG ZjQ eZShd aCNP GdOQL hcJH GQJLGdkG Qhi Yf QShd Gddg Udi Gddg Ydjg hSde Efg CeQ HJfGhd GdgfOHG ZjQ eZShd s
(3BNQgG (B:s
(3hHCf eYfi GdcdGe GdfHhi GdNGQL cKjQ efg eNQL GdCeKGd GdeVQhHg ai GdQehR GdhGbYI hdhGgH GdYbd s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdMGOjI hGdYTQhfs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B900s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(568) s
Keywords: (3GdWHs